LAMA PEMAKAIAN KONTRASEPSI SUNTIK 3 BULAN TERHADAP KEJADIAN MELASMA DI DESA KARANGJERUK KECAMATAN JATIREJO KABUPATEN MOJOKERTO - Sari Priyanti (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
Melasma is a problem for acceptor injections because melasma is very disturbing in terms of beauty and appearance, to the researchers wanted to know the extent of the effect of duration of use of contraceptive injections 3 months with the incidence of melasma in the village Karangjeruk Jatirejo District of Mojokerto in 2016. Observational analytic research with cross sectional approach, the population is acceptor injections of 3 months in the village karangjeruk districts Jatirejo mojokerto held on August 15 to September 15, 2016 the data obtained from the use of a long checklist and the incidence of melasma. Data were analyzed using chi-square with 38 respondents. Research cross-tabulation between duration of use on the incidence of melasma acceptor 3-month injections are mostly occurred in ≥ 5 years old usage is 17 respondents while the user is less than <5tahun many who did not have melasma incidence that is 11 respondents. Based on the results of statistical tests using Fisher's Exact Test showed that the p-value was 0.004 so that correlation the use of injections of 3 months with the incidence of melasma. For health workers, especially midwifery in an effort to improve services to acceptors in particular related to the treatment of side effects 3-month injectable contraceptive counseling are effective where the acceptor can change the way in the use of contraceptives after 5 years.